Conoce a los Pequenos Muppets - Gikow, Louise; Attinello, Lauren; Henson, Jim. (Mexico : Sitesa, 1989)
Kermit's cardboard box becomes a cave, space station, computer, piano, and castle when the Muppet Babies use their imagination.
Translation of: Meet the Muppet Babies